Age determination of red-spotted trout (Salmo macrostigma) inhabiting munzur stream, Turkey - Başusta, Asiye; Başusta, Nuri; Aydin, Rahmi; Ozer, Ebru I.; Girgin, Hulya (University of Punjab (new Campus), 2014)
The goal of this study was to determine the best bone structure for age determination in Salmo macrostigma. During the study, comparative age determinations were performed on a total of 243 fish samples by using the operculum, suboperculum, preoperculum, interoperculum and vertebrae bony structures. In comparing the ages of five bony structures, the least agreement was 90.79% at the ages of the interoperculum-vertebrae and preoperculum-interoperculum. The most agreement was 99.59% at the ages of operculum-suboperculum. The biggest age difference amongst bony structures was 2. The clearest age ring was observed on the operculum and suboperculum bones. © 2014 Zoological Society of Pakistan.
Keywords: Age determination; Red spotted trout; Salmo macrostigma